Trading practice and Behavioral Biases of Individual Investors in Nepalese Stock Market (Nepalese Journal of Management Research, 2021)
The paper was based on survey research design. There is significant association between experience group with herding bias and optimism bias and there is no significant association between experience group with investment decision bias, disposition effect bias, and overconfidence bias. Similarly there is significant association between trading frequency with herding bias, optimism bias, investment decision bias, disposition effect bias, and overconfidence bias. Heuristics may make investors overconfident as they overlook risks causing security price to move away from fundamentals. Investors tend to be overconfident and hence overestimate the accuracy of their forecast due to illusion of knowledge and illusion of control.